If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5y + -3 = 4(y + 3) Reorder the terms: -3 + 5y = 4(y + 3) Reorder the terms: -3 + 5y = 4(3 + y) -3 + 5y = (3 * 4 + y * 4) -3 + 5y = (12 + 4y) Solving -3 + 5y = 12 + 4y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-4y' to each side of the equation. -3 + 5y + -4y = 12 + 4y + -4y Combine like terms: 5y + -4y = 1y -3 + 1y = 12 + 4y + -4y Combine like terms: 4y + -4y = 0 -3 + 1y = 12 + 0 -3 + 1y = 12 Add '3' to each side of the equation. -3 + 3 + 1y = 12 + 3 Combine like terms: -3 + 3 = 0 0 + 1y = 12 + 3 1y = 12 + 3 Combine like terms: 12 + 3 = 15 1y = 15 Divide each side by '1'. y = 15 Simplifying y = 15
| (8x+9)(2x+4)=0 | | 5n+3+9= | | 3d^2-13d+12= | | r+(-2)=-8 | | 3=8-x | | -3b+7=8b-3 | | x^2=52-9x | | 7u+3-2(-2u-3)=2(u-3) | | z^4=-16i | | -4x+2=-7x+11 | | 3x(5x+36)=180 | | -16s-126+4(4s+32)=0 | | 8.1=x-12.5 | | 4x-8=x-5+3x | | 4x+2(-2x+7)=16 | | 16t^2+35t+5=0 | | 37-15x=8 | | 2x+0.33x=21 | | 13=-4t | | 4a-8whena=6 | | (5+4)[3+(8+5)]= | | 5z-13=-4z+14 | | 3x+12=6x-9x-12 | | 4(8-d)-50=20d-6(3+4d) | | y=sqrt(18x+9) | | 7x-2(x-6)=3 | | 3x+2=5y | | 4(x-5)+11=3(x+2)-3 | | 5(x+0.4)=5 | | 5x+11+119=180 | | 7(2x-1)=3 | | 3+13=2x |